1998
DOI: 10.1152/ajpregu.1998.275.2.r524
|View full text |Cite
|
Sign up to set email alerts
|

Systemic α-MSH suppresses LPS fever via central melanocortin receptors independently of its suppression of corticosterone and IL-6 release

Abstract: Systemically administered α-melanocyte-stimulating hormone (α-MSH) inhibits endotoxin (lipopolysaccharide; LPS)- or interleukin (IL)-1-induced fever and adrenocortical activation, but the sites of these actions and the mechanisms involved are unknown. The aims of this study were, first, to determine whether melanocortin receptors (MCR) located within the central nervous system mediate the suppressive effects of peripherally administered α-MSH on LPS-induced fever and activation of the pituitary-adrenal axis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…In addition, our research into the immunosuppressive activity of α-MSH and its importance in ocular immune privilege has demonstrated the dynamic contribution of the nervous system to immunoregulation. Further understanding of α-MSH immunomodulating activity will continue to promote the use α-MSH in a therapeutic manner to subdue inflammation and to manipulate immunity to prevent induction of inflammation resulting from specific infections and autoimmune diseases (Casalino-Matsuda et al, 2002;Colombo et al, 2002;Huang et al, 1998;Namba et al, 2002;Nishida et al, 2004;Shiratori et al, 2004). The effects of α-MSH on nitric oxide production by macrophages stimulated by specific TLR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our research into the immunosuppressive activity of α-MSH and its importance in ocular immune privilege has demonstrated the dynamic contribution of the nervous system to immunoregulation. Further understanding of α-MSH immunomodulating activity will continue to promote the use α-MSH in a therapeutic manner to subdue inflammation and to manipulate immunity to prevent induction of inflammation resulting from specific infections and autoimmune diseases (Casalino-Matsuda et al, 2002;Colombo et al, 2002;Huang et al, 1998;Namba et al, 2002;Nishida et al, 2004;Shiratori et al, 2004). The effects of α-MSH on nitric oxide production by macrophages stimulated by specific TLR.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we chose to compare the peripheral versus the central route of administration in these studies. Prior work has revealed that peripherally administered ␣-MSH can activate central processes related to the regulation of fever in rodents (42). In addition, peripheral administration of an MC4 receptor agonist produced substantial weight loss in POMC-deficient mice (15).…”
Section: Discussionmentioning
confidence: 99%
“…The superpotent ␣-MSH analog (Nle 4 ,DPhe 7 )-␣-MSH, was approximately 10 times more potent than ␣-MSH in reducing fever when given centrally . Fevers caused by endotoxin (Martin and Lipton, 1990;Goelst et al, 1991;Villar et al, 1991;Huang et al, 1998) and the cytokines IL-1 (Robertson et al, 1986;Daynes et al, 1987), IL-6 (Martin et al, 1991) and TNF (Martin et al, 1991), but not those caused by IFN-␣ (Hori et al, 1991) and prostaglandin E 2 (Davidson et al, 1992), were inhibited by ␣-MSH. The antipyretic message sequence of ␣-MSH (1-13) resides in the C-terminal tripeptide Lys-Pro-Val (Richards and Lipton, 1984b).…”
Section: Melanocortin Receptors and Control Of Inflammationmentioning
confidence: 99%